2017
DOI: 10.2298/sarh160209044d
|View full text |Cite
|
Sign up to set email alerts
|

Caries risk assessment in pregnant women using cariogram

Abstract: Introduction/Objective "Cariogram" takes into account interactions between caries-related factors and expresses a graphic assessment of the caries risk. The aim of this study was to evaluate the relationship between caries risk and different variables of Cariogram in pregnant women. Methods This study included 96 pregnant women. At baseline, data on general health, diet, oral hygiene, and fluoride exposure were obtained. DMFT (decayed, missing, and filled teeth) index was calculated by clinical examination. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
1
13
0
2
Order By: Relevance
“…With the instrument used to assess risk factors, the Caries Risk Assessment Tool, it was found that the group of pregnant women had a greater risk of caries compared to the control group where a moderate risk was found. In recent research the results were similar, concluding that pregnant women had higher risk of caries (Dolić et al, 2017;Molnar-Varlam et al, 2011;Pérez Oviedo et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…With the instrument used to assess risk factors, the Caries Risk Assessment Tool, it was found that the group of pregnant women had a greater risk of caries compared to the control group where a moderate risk was found. In recent research the results were similar, concluding that pregnant women had higher risk of caries (Dolić et al, 2017;Molnar-Varlam et al, 2011;Pérez Oviedo et al, 2011).…”
Section: Discussionmentioning
confidence: 74%
“…Although the Health Insurance Fund of Bosnia and Herzegovina covers full costs of dental care for children younger than 15-years, the ECC prevalence is extremely high and most of the lesions are untreated [3]. In countries like Bosnia and Herzegovina, with high caries prevalence, caries risk assessment is very important, but there is only data about caries risk assessment in the 12-years-old children [19] and pregnant women [30].…”
Section: Discussionmentioning
confidence: 99%
“…This longitudinal study was performed as a follow up of the study previously presented by Dolic et al [30]. The baseline survey was carried out in 2007 (January to April) and follow-up in 2011 (January to April).…”
Section: Study Groupmentioning
confidence: 98%
See 2 more Smart Citations